The Shifting Geopolitics of Russia's Natural Gas Exports and Their Impact on EU-Russia Gas Relations. Issue 4 (1st October 2016) - Sharples, Jack D.
ABSTRACT: In the sphere of natural gas, Russia and the EU share an interdependent relationship: Russia is the single largest supplier of natural gas to the EU, while the EU is Russia's largest gas export market. In May 2014, a deal was struck between Gazprom and the China National Petroleum Corporation to enable large-scale Russian gas exports to China. What impact could this deal have on the EU-Russia gas relationship? This article analyses Russia's existing and proposed gas production and export infrastructure for the delivery of natural gas to Europe and to China, and the extent to which increased gas exports to the East could result in the limitation of Russian gas exports to Europe. It is concluded that, due to its dependence on new gas production in eastern Siberia and the construction of new, purpose-built pipeline infrastructure, the Gazprom-CNPC deal of May 2014 will not have a significant impact on Russia's gas exports from north-western Siberia to the EU. The launch of talks aimed at delivering Russian gas from the Yamal Peninsula to China via the 'western route' opened the first possibility for Russia to balance its gas exports between East and West. However, this is unlikely to generate price competition between Europe and China, due to Gazprom's inability to extract a 'European' price for its gas exports to China. This suggests that Gazprom will not re-direct significant volumes away from Europe towards China, but rather will seek additional export volumes.